A Survey onadvances in security threats and its counter measures in cognitive radio networks - Ganesh, D; Pavan Kumar, T (International Journal of Engineering and Technology, 2018)
Cognitive radio is a promising wireless communication technology that improves spectrum utilization and offers many benefits for internet users. Cognitive radio networks utilizes the available limited resources in a more efficient and flexible way. The main objective of the Cognitive network is to efficiently utilize the unutilized spectrum and meet the demand of the secondary users. some of the important features of cognitive of Cognitive radio networks are dynamic spectrum access, self organizingÂ and flexibility. As Cognitive radio networks are flexible in nature, it will be effected by various security attacks which in turn affects the performance of the network. Furthermore Cognitive radio networks transmit the spectrum in several licensed bands and it also performs dynamic spectrum allocation. Cognitive radio and Cognitive radio networks are wireless in nature these face conventional attacks. In this survey we address variousÂ attacks in different layers , new threats and challenges that Cognitive networks face, current available solutions to address layer attacks. In addition applications, open problems and future Research challenges are also specified.